Effect of Diet on the Growth Performance, Feed Conversion, and Nutrient Content of the House Cricket. Issue 2 (27th March 2020) - Bawa, M; Songsermpong, S; Kaewtapee, C; Chanput, W
Abstract: The house crickets, Acheta domesticus, are sustainable and nutritious future sources of food, due to their nutritional benefits, particular high protein content and potential in solving global malnutrition. Different diets, particularly protein content, can influence the growth and nutritional value of crickets. The aim of this present study was to evaluate the effects of commercial diets and other formulated diets on the nutritional composition and growth parameters of the house crickets, being a major challenge to cricket's farmers in Thailand. Feed conversion ratio were 1.50, 1.50, and 1.51 for fed crickets on a blend of 22% protein and dry pulp pumpkin powder, fed 22% protein plus fresh pumpkin pulp, and fed 22% protein alone, indicated that these groups are high feed convertors and represented the quality of these diets compared to 1.73 and 1.81 for fed crickets on a blend of 22% and 16% protein, and those fed on 16% protein alone. Fed crickets on 22% protein had the highest amount of protein (76%), the lowest (48%) in those fed on 22% protein and fresh pumpkin pulp inclusion. The group on 22% protein diet also had the highest amount of phosphorus, potassium, calcium, and sodium. Fed 22% protein and either dry pulp pumpkin powder or fresh pumpkin pulp condition have shown improvement in vitamin B content. Crickets can effectively be produced on 22% protein diet to improve yield output and several minerals such as phosphorus, potassium, calcium, and sodium. In contrast, the supplementation of 22% protein diet with pumpkin ( Cucurbita maxima ) will improve vitamin B content.